Determinants of Exclusive Breastfeeding Practices among Mothers of 6-24 Months-Old Infants in Padang City, Indonesia - Helmizar; Elda, Frima; Rusdi, Faza Yasira; Sakinah, Restu (Media Gizi Indonesia, 2024)
The practice of exclusive breastfeeding (EBF) can reduce mortality and morbidity rates in children and supports optimal growth and development in children. The practice of EBF influenced by various predisposing factors, supporting factors and reinforcing factors. This study aimed to evaluate the determinants of exclusive breastfeeding practices among mothers of infants 6-24 months old infants in Padang. This case control study conducted at Padang with 200 mothers, consisting of 100 mothers of case groups and 100 mothers of control groups. Maternal and infant characteristics, family characteristics, predisposing factors, supporting factors and reinforcing factors, and exclusive breastfeeding were collected for this study. Chi square and binary logistic regression were used to the data analysis. Results showed that mother's occupation, exclusive breastfeeding knowledge and parent's support were the most influencing determinants for exclusive breastfeeding.